Digital Content Marketing – A Literature Review on Concepts, International Experiences and Implications for Vietnam - Quy Nguyen Hong (EDP Sciences, 2021)
Communication activities are increasingly more diverse, complex and play a more important role in brand building. Perceived consistency of brand messages (across campaigns), a new variable that reflects an important aspect of the integration performance of marketing communications, has been included in the investigation of the impact of marketing communications. It has been shown that perceived consistency strongly correlates with brand's perception, attitude and behavior changes of the target audience. However, the mechanism of influence of this factor in the communication process is still a question for further research.